CHARACTERIZATION OF NITROGEN-FIXING CYANOBACTERIAL CONSORTIA ISOLATED FROM THE RHIZOSPHERE OF CARICA PAPAYA - DÍAZ, YADENIS ORTEGA (2024)
NITROGEN-FIXING CYANOBACTERIAL CONSORTIA ARE AN ALTERNATIVE TO THE INDISCRIMINATE USE OF CHEMICAL FERTILIZERS THAT AFFECT THE ENVIRONMENT, FIX ATMOSPHERIC NITROGEN, AND CAN THEREFORE BE USED AS PLANT GROWTH PROMOTERS, SYNTHESIZE VARIOUS SUBSTANCES SUCH AS AUXINS, VITAMINS, AND TOTAL PROTEINS, AND FIX ATMOSPHERIC BIOFERTILIZERS AND SOIL CONDITIONERS. THE PRESENT STUDY AIMED TO OBTAIN AND DEVELOP, BY BIOTECHNOLOGICAL MEANS, TWO CONSORTIA OF CYANOBACTERIA ISOLATED FROM THE ROOT AND RHIZOSPHERE OF CARICA PAPAYA GROWN IN SANDY LOAM SOIL. THE CULTURE WAS CARRIED OUT IN BLUE GREEN MEDIUM WITHOUT MODIFIED NITROGEN (BG110), WITH AERATION OF 0.32 L MIN−1, AT A LIGHT INTENSITY OF 48.83 ΜEM−2S−1, AND A TEMPERATURE OF 22 ± 2 °C. TWO CONSORTIA CONSISTING OF NOSTOC COMMUNE, APHANOTHECE MINUTISSIMA, PLANKTOTHRIX SP. (C1), NOSTOC COMMUNE, CALOTHRIX SP., AND APHANOTHECE MINUTISSIMA (C2) WERE ISOLATED AND MORPHOLOGICALLY IDENTIFIED. THE EFFECTIVE DEVELOPMENT OF THESE CONSORTIA WAS VERIFIED AT THE LABORATORY LEVEL BY OBTAINING BIOMASS IN DRY WEIGHT AS WELL AS PHOTOSYNTHETIC PIGMENTS, PROTEINS, CARBOHYDRATES, AND LIPIDS. GERMINATION PARAMETERS WERE DETERMINED IN SEEDS OF CUCUMIS SATIVUS L. VAR. MARKET PLUS TREATED WITH THE NITROGEN-FIXING CYANOBACTERIA CONSORTIA, OBTAINING A HIGHER GERMINATION PERCENTAGE (>90%), GREATER ROOT LENGTH (>6 CM), AND HIGHER VIGOUR INDEX I (513), II (13.02) FOR THE C2 CONSORTIUM. THIS BROADENS THE SPECTRUM OF RHIZOSPHERE-DERIVED MICROORGANISMS WITH POTENTIAL AS GROWTH BIOSTIMULATORS. © 2024 BY THE AUTHORS.